2017
DOI: 10.1038/ncomms15000
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-23a cluster promotes osteocyte differentiation by regulating TGF-β signalling in osteoblasts

Abstract: Osteocytes are the terminally differentiated cell type of the osteoblastic lineage and have important functions in skeletal homeostasis. Although the transcriptional regulation of osteoblast differentiation has been well characterized, the factors that regulate differentiation of osteocytes from mature osteoblasts are poorly understood. Here we show that miR-23a∼27a∼24-2 (miR-23a cluster) promotes osteocyte differentiation. Osteoblast-specific miR-23a cluster gain-of-function mice have low bone mass associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 31 publications
(45 reference statements)
2
66
0
1
Order By: Relevance
“…On the other hand, the downregulated miRNAs, eg, let‐7/miR‐98, were predicted to target and repress mRNA expression of osteocyte‐specific dentin matrix protein 1 (DMP1). Consistently, another study conducted by Zeng and colleagues showed that the miR‐23a cluster, containing miR23a, miR27a and miR24‐2, could promote osteocyte differentiation. By genetic approach, they found that the osteoblast‐specific miR‐23a cluster gain‐of‐function mice exhibited low bone mass associated with decreased osteoblast but increased osteocyte numbers, whereas the loss‐of‐function transgenic mice overexpressing miRNA decoys for either miR‐23a or miR‐27a showed decreased osteocyte numbers.…”
Section: Mirna and Osteocytessupporting
confidence: 67%
“…On the other hand, the downregulated miRNAs, eg, let‐7/miR‐98, were predicted to target and repress mRNA expression of osteocyte‐specific dentin matrix protein 1 (DMP1). Consistently, another study conducted by Zeng and colleagues showed that the miR‐23a cluster, containing miR23a, miR27a and miR24‐2, could promote osteocyte differentiation. By genetic approach, they found that the osteoblast‐specific miR‐23a cluster gain‐of‐function mice exhibited low bone mass associated with decreased osteoblast but increased osteocyte numbers, whereas the loss‐of‐function transgenic mice overexpressing miRNA decoys for either miR‐23a or miR‐27a showed decreased osteocyte numbers.…”
Section: Mirna and Osteocytessupporting
confidence: 67%
“…It should be noted that several of the miRNAs with a positive correlation with BMD also promote osteogenesis in vitro; eg, iliac bone miRNAs: miR‐29a‐3p, miR‐28‐5p, miR‐181a‐5p, and miR‐27a‐5p; femoral bone miRNAs: miR‐335‐5p, miR‐194‐5p, and miR‐378a‐5p, as well as miR‐29c‐3p (in femoral and iliac bone) . It is noticeable and of potential importance that most of the osteogenesis‐associated miRNAs inversely correlated to BMD are found in iliac bone, whereas most of the osteogenic miRNAs positively correlated to BMD, are detected in femoral bone.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is shown that BMP2 can induce the osteoclast activity and the remodeling process of fracture healing [20]. And a recent study reported that the expression of BMP2 was significantly decreased in patients with bone none union compared with fracture healing patients [21]. Therefore, BMP2 is a key target gene for fracture healing and the formation of callus.…”
Section: Ivyspringmentioning
confidence: 99%